‘Let’s Grow Together’: Understanding the Current Provision of Early Childhood Development and Education for Children with Disabilities in Rural Malawi through Community-based Participatory Research - and Greenwood, Margo; Gercama, Ingrid; Lynch, Paul; Moore, Katie; Mankhwazi, Mika; Mbukwa, Jenipher; Bedford, Juliet (International Journal of Disability, Development and Education, 2022)
Focussing on the experiences and perceptions of parents and volunteer caregivers of children with disabilities, this paper reports on a study that explored the provision of early childhood development and inclusive education for children with disabilities in rural Malawi. Drawing on a community-based participatory research (CBPR) design, ten local community researchers and two Malawian researchers collaborated to interview forty caregivers and parents of children with disabilities attending ten Community Based Care Centres (CBCCS) in Southern Malawi. Findings are reported through four key themes: experiences of disability, inclusion, learning and developmental progress; factors influencing non-enrolment and absenteeism; barriers to learning and progress; and accountability and support channels. Five key components were highlighted: 1) relevance of peer interactions for learning outcomes and wellbeing; 2) the importance of the CBCC as (a model for) a safe space against discrimination; 3) relevance of quality education and pre-school teacher training; 4) necessity of material support to decrease absenteeism; 5) the need for greater community and state support for children with disabilities. The implications of the study’s findings are discussed, including the importance and relevance of considering the perspectives of community based actors in program and policy design.
Keywords: Disability; Malawi; early childhood development; education; health; inclusion; participatory research